New records, descriptions and notes on Encyrtidae (Hymenoptera: Chalcidoidea) from Iran - Guerrieri, Emilio; Ghahari, Hassan (Zootaxa, 2018)
New additions to the Iranian fauna are reported. Three new species of Encyrtidae, Anagyrus osmoi sp. nov., Metaphycus prengoi sp. nov., and Microterys obricoi sp. nov., are described. Three new records, Anagyrus saccharicola Timberlake, 1932, Copidosoma filicorne (Dalman, 1820) and Paranathrix acanthococci (Myartseva, 1977) and one note are reported.